HEALTH EDUCATION AND MONITORING IN DIABETIC PATIENTS TO IMPROVE QUALITY OF LIFE - Agnes Lia Renata; Khossy' Afrohhatunnisa; Cici Idela; Rahmaisynta Putri Rindharso; Windy Maharani Nirmala; Ajeng Ayu Larasati; Delfina Yolanda Saputri (Poltekkes Kemenkes Semarang, 2025)
The results of the Basic Health Research (RISKESDAS) in 2018 showed that 67.8% of the Indonesian population aged more than 15 years experienced periodontal disease such as periodontitis. The incidence of periodontitis disease can occur and become more severe in the presence of systemic factors such as diabetes mellitus. People with diabetes mellitus experience several health complications caused by increased blood sugar levels, blood vessels, and nerves, including the gums. This can weaken the bone surrounding the teeth and gums, and increase the risk of other oral diseases, such as tooth loss and dental caries caused by the weakening of tooth attachment to the gums and a decrease in the rate of saliva in the mouth. Efforts to prevent the occurrence of periodontal disease and other oral and dental disease infections in patients with diabetes mellitus are by conducting health education and monitoring programs for patients. The goal is to increase knowledge, willingness, awareness, compliance and community participation in maintaining and maintaining dental health independently. The methods used in this service are interviews, observations and the implementation of training and health monitoring for respondents. Based on the results of the activities that have been carried out in the service, the respondents gave a positive response and there was an increase in knowledge, awareness and motivation in maintaining their health